Potensi Bakteri Probiotik Indigenous Lactobacillus Plantarum Dad-13 Sebagai Starter Pada Pembuatan Yoghurt Fungsional: Kajian Pustaka - Husnita Komalasari; Wahyu Krisna Yoga (Food Scientia : Journal of Food Science and Technology, 2022)
Yoghurt is a dairy product that is fermented using one or more bacteria called a starter. This study aims to determine the potential of indigenous bacteria Lactobacillus plantarum Dad-13 as a starter in the production of yoghurt functional. The method in this research is a literature study that comes from Google Scholar, Science Direct, Pubmed dan Research Gate. The selection of cited journals has gone through a screening process based on inclusion, special and exclusion criteria. Generally, the bacteria were used as starters in yoghurt production are Lactobacillus bulgaricus and Streptococcus thermophilus. One of the indigenous bacteria from Indonesia that has a potential to be used as a starter is Lactobacillus plantarum Dad-13. Based on various previous studies, these bacteria are able to produce yoghurt products with good physicochemical and organoleptic properties. The use of Lactobacillus plantarum Dad-13 as a starter can increase the functional properties of the resulting yoghurt product. These bacteria are able to produce high levels of folate in yoghurt and one of probiotic bacteria that has been tested for its effectiveness and benefits for health. It is stated that yoghurt and probiotics are included in functional foods. Based on the literature review data that has been carried out, the use of these bacteria has the potential to produce yoghurt products with high functional properties and beneficial for health.